A formação para pesquisa no curso de Pedagogia da Universidade Federal de Alagoas - Azevedo, Raissa Medeiros Frazão de (2019)
Initial teacher training has been identified as the locus for the future teacher to develop the practice of research, so this study was dedicated to investigate how the research is constituted in the formative dimension of the Pedagogy course of the Federal University of Alagoas. As a theoretical perspective, reflections on teacher education based on the studies of Dewey (2010), Imbernón (2001), Tardif (2000), Gauthier (1998) and Maldaner (2006) were discussed; The concept of research professor that had as precursor studies by Stenhouse (1991), and Antonio Nóvoa (1992); The research of Professor X the academic research directed in the studies of Zeichner (2008), Lüdke (2001) and Garcia (2009); The relationship between teacher researcher and reflective teacher present in the studies of Schon (1998) and Perrenoud (1993) and the analysis of the guiding documents of the course (DCNS and PPC). The methodology used refers to qualitative research, and the case study is used as a methodological approach. Data were obtained through semi-open questionnaires applied to students from the 4th to 9th period of the UFAL Pedagogy course. The analysis of the data revealed that there are convergences and divergences between the guiding documents and the training for research in the Pedagogy course. Thus, it was verified the need to update the Pedagogical Project and the completion / integration of the research in the disciplines and other actions of the course. This research also made possible the reflection about the valorization of the research posture as crucial for the production and socialization of knowledge, as well as for the development of the cultural patrimony of the agents involved in the research during the formation.